EVALUATION OF EAZY PASSPORT ACTIVITIES AS AN ALTERNATIVE FORM OF SERVICE DURING THE COVID-19 PANDEMIC BY IMMIGRATION POLYTECHNIC CADETS - Bagus Muahamad Iskandar; Rasona Sunara Akbar (Jurnal Abdimas Imigrasi, 2021)
At the beginning of 2020 the whole world was in an uproar with the emergence of a virus that can attack the respiratory tract and can even make its victims die. Covid-19 or Corona Virus is the cause. When entering the end of 2019 in December the first Covid-19 cases appeared in the city of Wuhan, China (People's Republic of China). This virus spreads very quickly through droplets or fluids. At the beginning of March 2020, Covid-19 cases had started to enter Indonesia, precisely in Depok City. It is reported that there are 2 people who have contracted Covid-19.. People began to self-quarantine at home, and always maintain cleanliness by washing hands and using hand sanitizer. Some people even spray disinfectant in their homes to kill the Covid-19 virus. The government has also stepped in to tackle this problem. The government asks residents to always comply with health protocols and use masks and reduce activities outside the home if it is not too urgent. The Indonesian Directorate General of Immigration issues policies related to making passports during the pandemic, such as limiting the number of passport applicants in the immigration office. Applicants are also required to follow the health protocol rules set by the immigration authorities.